Characteristics of Yoga Practitioners, Motivators, and Yoga Techniques of Choice: A Cross-sectional Study - Telles, Shirley; Sharma, Sachin Kumar; Singh, Nilkamal; Balkrishna, Acharya (Frontiers in Public Health, 2017)
Background The characteristics of yoga practitioners and factors motivating people to practice yoga have been studied in the US and in Australia. This study aimed to determine the characteristics of yoga users in India, the factors that motivate them to practice yoga, and the yoga techniques of choice. Materials and methods The study was a one-time, cross-sectional survey based on convenience sampling. Inclusion criteria were (a) a minimum of 1 week experience of yoga and (b) at least 10 years of age. 14,250 people received the survey. After excluding those who did not meet the inclusion criteria or filled in the survey incompletely or incorrectly, 5,157 respondents were included in the study. Results Out of 5,157 respondents, there were more males (67.3%), aged between 21 and 44 years (33.7% of the sample surveyed), educated up to high school (62.5%), students (39.3%), and those who had between 1 and 12 months of experience in yoga (54.4%). The first most common reason to practice yoga for all respondents was physical fitness. Three of the remaining reasons to practice yoga differed significantly with age: (i) yoga for disease management (χ2 = 17.62, p < 0.005), (ii) yoga as a hobby (χ2 = 10.87, p < 0.05), and (iii) yoga based on the guru’s (teacher’s) instructions (χ2 = 20.05, p < 0.001). The yoga technique of choice [i.e., (i) asanas (χ2 = 23.17, p < 0.001), (ii) pranayama (χ2 = 19.87, p < 0.001), or (iii) meditation (χ2 = 9.64, p < 0.05)] differed significantly across age groups. Conclusion In India, a yoga practitioner was more likely to be male, between 21 and 44 years of age, high school educated, and a student. The reasons to practice yoga and the yoga technique of choice differed significantly with age.